2019
DOI: 10.1002/jemt.23408
|View full text |Cite
|
Sign up to set email alerts
|

Seed morphology using SEM techniques for identification of useful grasses in Dera Ghazi Khan, Pakistan

Abstract: In recent study, 15 taxa of family Poaceae from Dera Ghazi Khan were investigated for morphological characterization of seeds. Scanning electron microscopy (SEM) was utilized to study morphological features of grass seeds. Moreover, economic importance of studied taxa has been discussed in present research. Grass seeds or caryopsis were collected in their mature state from different areas of Dera Ghazi Khan. Collected caryopses were subjected to SEM to investigate surface sculpture, epidermal cell shape, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Previously, much work has been conducted on systematics to identify different species by seed characters using SEM ( Ahmad et al, 2020 ), but there has been little reports on the correlation between seed internal ultrastructure and persistence. It was observed that ABA produced by seed embryos contributed to germination arrest upon imbibition and then maintained viability ( Chahtane et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, much work has been conducted on systematics to identify different species by seed characters using SEM ( Ahmad et al, 2020 ), but there has been little reports on the correlation between seed internal ultrastructure and persistence. It was observed that ABA produced by seed embryos contributed to germination arrest upon imbibition and then maintained viability ( Chahtane et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Pakistan various studies have been conducted on microscopic characterization of plant species. The light and scanning microscopic characterization of various groups has been done on various groups of plants (Bano et al, 2020; Ahmad et al, 2013; Ahmad et al, 2020; Ahmad et al, 2020; Ashfaq et al, 2020a) while microscopic characterization of specific groups include Bryophytes (Khan et al, 2020); Gymnosperms (Khan et al, 2019); Pteridophytes (Shah et al, 2020; Shah et al, 2020; Shah et al, 2021); Some of the specific families including Asteraceae (Ahmad et al, 2013; Bano, Ahmad, Zafar, Sultana, & Khan, 2015; Ayaz et al, 2019); Mimosaceae (Khan et al, 2019; Alam et al, 2019; Khan et al, 2021); Convolvulaceae (Ashfaq et al, 2020b); Cactaceae (Majeed et al 2020); Capparidaceae (Mir et al, 2019); Amaranthaceae (Hussain et al, 2018; Nazish et al, 2020); Acanthaceae (Raza et al, 2020); Caryophyllaceae (Ullah et al, 2016; Ullah et al, 2019); Poaceae (Shaheen et al, 2018; Ullah et al, 2016; Khan et al, 2019; Usma et al, 2019; Ahmad 2020; Ullah et al, 2021); Lamiaceae (Gul et al, 2021; Bano et al, 2020); Papilionoideae (Rashid et al, 2019; Rashid et al, 2021; Waheed et al, 2021); Eragrostideae‐Poaceae (Ahmad et al, 2011); Solanaceae (Kayani et al 2019; Ashfaq et al, 2020a); Papilionaceae (Bano et al, 2019); Apiaceae (Kalsoom et al, 2019); Vitaceae (Lubna et al, 2019); Balsaminaceae (Rahman, Ahmad, Zafar, Mumtaz, & Shah, 2017); Caesalpiniaceae (Ullah et al, 2019); Euphorbiaceae (Zahra, Ahmad, Shinwari, Zafar, & Sultana, 2014). However, no work has been done on identification of A. flavus in various areas of Pakistan using microscopic techniques especially SEM.…”
Section: Introductionmentioning
confidence: 99%
“…Micromorphological character of seeds are studied through SEM which is less costlier, most reliable, easy, and time saving as compared to other modern techniques (Ayaz et al, 2020;Aziz et al, 2021;Rashid et al, 2021). The surface morphology of proposed green nanocatalyst has been determined using SEM technique which has been proved very effective in the field of plant taxonomy because it is used to explore the surface features of vegetative and reproductive organs (Ahmad et al, 2020;Usma et al, 2019). It also helps to illustrate the variations in seeds among the different member of the same family.…”
Section: Introductionmentioning
confidence: 99%